Navigation Based on Distance and Speed Required on Road - Gaharwar, Raina D; Patel, Birajkumar V (International Journal of Computer Sciences and Engineering, 2019)
Vehicle drivers uses Google Maps (Navigator) during their travelling to get exact road map with proper direction including distance in km and total time remaining to reach out destination. For that people need to have facility like, inbuilt GPS system in vehicle or cell phone with internet connectivity. GPS (Global Positioning System) basically works with satellite in orbit. It is used to determine location of user vehicle. For this user must require having GPS in hand set. Problem with existing navigator is, it is providing shortest path routes to traveller and that creates problem for traveller. Sometimes shortest path with slow speed road creates problem of delay in travelling also. So, solution with speed on road acknowledgement required. For that in this paper algorithm is provided for solving this problem.